Performance of red pigment production by Monascus purpureus at different extraction methods - Sharifah Shufiza Khaziri, Tuan Hadi (2013)
The purpose of this research is mainly to study the performance of red pigment production at different extraction methods. The strain used in this study is Monascus purpureus which produce red pigment and red yeast rice was used as the substrate in the solid state fermentation. The initial moisture content in fermentation would be 56% which was considered as optimal pigmentation to be occurred. It would then be inoculated with 1x107 spore/ml suspension of inoculum. Extraction methods including solvent extraction, Soxhlet extraction, agitated extraction and ultrasonic extraction were being carried out after fermentation process complete. Each methods required several conditions to be fulfilled to achieve the objective of this research. In this study, the best solvent used was 60% ethyl alcohol. Uv-Vis spectrophotometer is used to analyze red pigments in the extracts which were quantified by reading the absorbance at wavelength of 500 nm for this pigment. Thus, the best performance of the methods was identified by maximum extracts achieved which was measured by concentration of extracted product obtained. Solvent extraction was used as the reference and this method produced 1.278AU/g.d pigment extract. The results were 1.268AU/g.d for ultrasonic extraction, 1.265AU/g.d for agitated extraction and 0.128AU/g.d for Soxhlet extraction. The best method was ultrasonic extraction as compared to solvent extraction in a separate experiment and it produced 0.920AU/g.d than in solvent extraction, 0.869 AU/g.d pigment extract. The increrment percentage was about 5.81%. Besides, an analysis of variance (ANOVA) was carried out to investigate the significance to use the methods, showing the p-value. The p-value for agitated extraction was 3.63x10-7, 8.35x10-8 for ultrasonic extraction and 3.79x10-7 for Soxhlet extraction. All of the methods were significant to be carried out since all of the p-value was lower than 0.05.